ULAMA ARAB DI TANAH MELAYU: SATU ANALISA PADA AWAL ABAD KE-20 - Farid Mat Zain; Nurulwahidah Fauzi (UIN Sunan Kalijaga Yogyakarta, 2014)
Arab community groups who migrated to the Archipelago through trade and propagation of Islam has been assimilated into the local community in helping the development of Islamization of Sciences. This paper seeks to explore their migration to the Malay Land along 20th centur y and to explore the involve- ment of scientists that has been involved in administrative affairs and Islamic education in the life of the local community.